2014
DOI: 10.1111/ijfs.12590
|View full text |Cite
|
Sign up to set email alerts
|

Properties of low methoxyl pectin‐carboxymethyl cellulose based on montmorillonite nanocomposite films

Abstract: In this study, the low methoxyl pectin-carboxymethyl cellulose-based montmorillonite (LMP-CMC-MMT, LCM) nanocomposite films with nine ratios of LMP:CMC (from 10:0 to 0:10) and different MMT contents (1-8 wt%) were prepared. The mechanical properties, colour, opacity and water vapour permeability (WVP) of composite films were investigated. The maximum of tensile strength (TS) of composite films was 39.85 AE 2.51 MPa at LMP:CMC ratio of 4:6 and 4 wt% MMT (LCM47), which indicated the formation of hydrogen bonds b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
3
17
1
Order By: Relevance
“…There was not any direct report about WVP of MC-MMT films in other papers, while Turhan and Sahbaz [32] reported WVP of MC films (without MMT) around 0.4 9 10 -3 g/m h KPa, which was nearly like the obtained result in present research [32]. Yu et al [33] announced that WVP of carboxymethylcellulose films with 4% MMT was 0.8 9 10 -5 g/m h KPa. The difference of the basic polymers and the presence of glycerol are the main reasons of higher WVP in present study.…”
Section: Wvpsupporting
confidence: 68%
See 2 more Smart Citations
“…There was not any direct report about WVP of MC-MMT films in other papers, while Turhan and Sahbaz [32] reported WVP of MC films (without MMT) around 0.4 9 10 -3 g/m h KPa, which was nearly like the obtained result in present research [32]. Yu et al [33] announced that WVP of carboxymethylcellulose films with 4% MMT was 0.8 9 10 -5 g/m h KPa. The difference of the basic polymers and the presence of glycerol are the main reasons of higher WVP in present study.…”
Section: Wvpsupporting
confidence: 68%
“…Rodriguez et al [39] reported that b* of cellulose acetate with 7.5% MMT was 1.6 and Yu et al [33] announced that the b* of carboxymethylcellulose with 8% MMT was 0.09, while in present research the maximum b* (3.475; 60 min) was outstandingly higher than the other reported values. Tunc and Duman [6] reported the opacity of MC-MMT films (with 20% MMT) around 6.7.…”
Section: Optical Properties Of Mc-mmt Filmscontrasting
confidence: 59%
See 1 more Smart Citation
“…Yu et al [15] varied the ratio between LM pectin and CMC to prepare nanocomposites by adding up to 8% w/w of montmorillonite reinforcement to the solutions. The tensile strengths of the unreinforced polymers were measured from approximately 16 to 32 MPa, and with reinforcement the tensile strength increased.…”
Section: Mechanical Analysis Of Orange Waste Filmsmentioning
confidence: 99%
“…Nevertheless, pectin-based composites have been prepared with different reinforcing substances [12] and cellulosic plant fibres have 2 International Journal of Polymer Science certainly been of great interest because of their favourable mechanical properties as a potential substitute for glass fibres [13] in biocomposites. Cellulose reinforced pectin composites have been developed, for example, for tissue engineering applications [14] and for food packaging applications [15] from commercial sources. However, there is no study on directly using cellulosic fibres and pectin obtained from citrus waste to prepare a biofilm.…”
Section: Introductionmentioning
confidence: 99%